A STUDY AND IMPLEMENTATION ON DATA MINING TECHNOLOGY AND APPLICATIONS FOR ANALYSIS ON SALES PRODUCTIVITY - Johar,; MGM,; Yajid, Mohd Shukri Ab; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
This project focuses on the study of Data Mining technology and implementation of product sales predictive analysis for Amway (M). Certain parts have been adopted to enumerate the grounds of study, where at this stage mainly books, journals and articles on the Internet about Data Mining, as well as interviews and observations have been performed to gather the data of Amway (M). After the collection of data, model was developed to interpret the significance of results performed on the basis of such data by integrating automation, visual representation and predictive analysis into business processes, companies can enhance the efficiency and accuracy of decision making by appropriate methodology. Lastly, regarding this project the author has learned a lot upon the completion of it. It has been, thus, a very satisfactory and fruitful journey of completing this project. Generally, this whole project needs to be polished to have a better effect.